Exploring Experiences and Perceptions of Aging and Cognitive Decline Across Diverse Racial and Ethnic Groups. (15th July 2015) - Roberts, Lisa R.; Schuh, Holly; Sherzai, Dean; Belliard, Juan Carlos; Montgomery, Susanne B.
Objective: To explore how older adults from three prominent ethnoracial groups experience cognitive decline and aging.Method: Semistructured key informant interviews (KIIs) and focus groups (FGs) were conducted with caregivers, experts, and older adults.Results: ( N = 75). Fifteen KIIs regarding cognitive aging issues were conducted among health care professionals and community-based agencies serving older adults. Eight FGs included family caregivers and physicians, and six FGs with Latino, African American, and White older adult community members. Major themes included (a) personal expectations about aging, (b) societal value of older adults, (c) model of care preferred, and (d) community concerns. An overarching theme was a sense of loss associated with aging; however, how this loss was experienced and dealt with varied.Discussion: Distinct patterns of concerns and views are important to understand for the development of programs aimed at meeting the needs of diverse older adult community members to improve health outcomes.